Posteljica - Cör, Andrej (Medicinski razgledi, 2006)
The placenta is crucial for fetal survival, growth and development. After the baby has been born the role of the placenta is finished, however, it is essential that delivering physician perform a thorough, accurate examination of it. With this examination it is possible to get information that may be important to the care of both mother and infant. To recognise numerous potential abnormalities of placenta, normal morphology, origin and developmentshould be known. It is the purpose of this article to describe the morphological characteristics of normal placenta, the way haw placenta arise and develop from blastocyst implantation till birth. Some recent findings about cells that compose the placenta are presented as well. Despite accurate examination of the placenta in the delivery room, it should be submitted for pathological evaluation if an abnormality is detected or certain indications are presented.
Keywords: Placenta; Placenta, bolezni; Plodov razvoj; Umbilical Cord; Trophoblast; Popkovnica; Fetal Development; Trofoblast; Placenta Diseases; porodništvo; embrionalni razvoj